2014
DOI: 10.1073/pnas.1406847111
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide high-resolution mapping of chromosome fragile sites in Saccharomyces cerevisiae

Abstract: In mammalian cells, perturbations in DNA replication result in chromosome breaks in regions termed "fragile sites." Using DNA microarrays, we mapped recombination events and chromosome rearrangements induced by reduced levels of the replicative DNA polymerase-α in the yeast Saccharomyces cerevisiae. We found that the recombination events were nonrandomly associated with a number of structural/sequence motifs that correlate with paused DNA replication forks, including replication-termination sites (TER sites) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(115 citation statements)
references
References 53 publications
(71 reference statements)
8
107
0
Order By: Relevance
“…Most of the statistical tests followed the methods described in our previous studies (10,41). Briefly, χ 2 tests were performed using VassarStat (vassarstats.net) or the chisq.test functions in Excel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the statistical tests followed the methods described in our previous studies (10,41). Briefly, χ 2 tests were performed using VassarStat (vassarstats.net) or the chisq.test functions in Excel.…”
Section: Methodsmentioning
confidence: 99%
“…We applied this method to map events associated with low DNA polymerase α, and showed that LOH events were often associated with chromosome elements [such as quadruplex motifs, termination (ter) sequences, and long-terminal repeats (LTRs)] that slow replication forks (10).…”
mentioning
confidence: 99%
“…However, it has also been recognized that HR also has the potential to induce genome instability, acting inappropriately or in an unregulated fashion (Elliott and Jasin 2002;Kolodner et al 2002). For example, ectopic recombination between repeated DNA is a potent driver of chromosomal rearrangements, as suspected from genomic analysis and established in genetic model systems (Szankasi et al 1986;Cooper et al 1997;Agarwal et al 2006;Haber 2006;Weinstock et al 2006;Putnam et al 2009;Song et al 2014). Furthermore, the identification of synthetic lethality in double mutants that depend on HR, called recombination-dependent lethality, shows that uncontrolled HR leads to potentially toxic intermediates and cell death (Heude et al 1995;Schild 1995;Gangloff et al 2000;Fabre et al 2002;Bastin-Shanower et al 2003).…”
Section: Quality Control By Pathway Reversibilitymentioning
confidence: 99%
“…In previous studies of chromosome rearrangements in yeast strains with low levels of DNA polymerase a (Song et al 2014), we found deletions and duplications in addition to other types of changes. Most of these events were a consequence of homologous recombination between Ty elements or other dispersed repeats.…”
Section: Discussionmentioning
confidence: 53%
“…Although simple nondisjunction events would be expected to produce equal frequencies of trisomies and monosomies, the relative growth rates of trisomic and monosomic strains might skew the ratio of these events. It is unlikely that this factor is completely responsible for our observations, since we previously showed that, in yeast strains with low levels of DNA polymerase a, monosomic strains were five times more frequent than trisomic strains (Song et al 2014).…”
Section: Discussionmentioning
confidence: 79%